2013
DOI: 10.1590/s0100-83582013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Competitive ability of soybean cultivars with horseweed (Conyza bonariensis)

Abstract: -The existence of large areas infested with populations of Conyza spp. resistant to glyphosate in Brazil demands appropriate and integrated management strategies. This experiment aimed to identify soybean cultivars with greater competitive ability with horseweed plants and to determine plant characteristics associated with this ability. The experiment was arranged in a randomized complete block design with split plots. , transplanted seven days before soybean planting) in the subplots. The average yield loss d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
(11 reference statements)
2
23
0
1
Order By: Relevance
“…This information shows how much horseweed may adversely affect the soybean crop, confirming information reported by Gazziero et al (2010), Patel et al (2010) and Trezzi et al (2013), and demonstrating that effective control measures must be taken to remedy and/or reduce the losses caused by this invasive species. Accordingly, among the herbicidal treatments, chlorimuron-ethyl scored significantly lower grain yield than cloransulam-methyl in all studied doses.…”
supporting
confidence: 86%
“…This information shows how much horseweed may adversely affect the soybean crop, confirming information reported by Gazziero et al (2010), Patel et al (2010) and Trezzi et al (2013), and demonstrating that effective control measures must be taken to remedy and/or reduce the losses caused by this invasive species. Accordingly, among the herbicidal treatments, chlorimuron-ethyl scored significantly lower grain yield than cloransulam-methyl in all studied doses.…”
supporting
confidence: 86%
“…In an experiment conducted by TREZZI et al (2013) on the competitive ability of soybean cultivars in competition with hairy fleabane, the authors have verified that soybean height can be higher in the presence of the weed, a phenomenon referred to as initialism (VIDAL, 2010). RY for TDM of soybean in competition with hairy fleabane rosette showed a convex line, which indicates an advantage in growth compared with the estimated straight lines, and hairy fleabane showed a concave line, hence its growth was affected by competition with soybean (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Trezzi et al (2014) emphasize that, in no-tillage system, the chemical control of weeds before sowing is fundamental to avoid yield losses in the crops. Studies conducted by Trezzi et al (2013) demonstrated that the presence of 13 horseweed plants m -2 was able to reduce soybean yield by 25%. Although the mean value of horseweed plants is below 13, in some sampling points the density was 80 plants m -2 , which can reduce soybean yield to zero.…”
Section: Resultsmentioning
confidence: 99%